Pengaruh Brand Ambassador Sehun Exo terhadap Minat Beli Konsumen Melalui Brand Image (Studi Kasus Brand Whitelab) - Retno Adiningsih; Akhmad Yunani (J-MAS (Jurnal Manajemen dan Sains), 2023)
The local beauty industry is at the peak of its popularity, which is marked by the increasing presence of skincare and makeup brands. Whitelab is a company in the skincare sector implementing a marketing strategy by making Sehun EXO a brand ambassador to be able to influence someone. This is one way for the Whitelab brand to attract consumers. The purpose of this study is to find out how brand ambassadors, purchase intentions, and brand image on Whitelab products, determine the influence of brand ambassadors on brand image, brand ambassadors on purchase intentions, and the influence of brand ambassadors on purchase intentions through brand image. This study uses descriptive analysis and casual relationships, technically using path analysis models and Sobel tests with a total sample of 100 respondents. The population in this study is every individual who knows the Whitelab brand and knows Sehun EXO as the Whitelab brand ambassador. The results of the study show that the Brand ambassador variable has a significant effect on Brand image, the Brand ambassador variable has a significant effect on Purchase intention, and the Brand ambassador variable has a significant effect on Purchase intention through Brand image.